2000
DOI: 10.1074/jbc.275.5.3288
|View full text |Cite
|
Sign up to set email alerts
|

Mapping of Eps15 Domains Involved in Its Targeting to Clathrin-coated Pits

Abstract: Clathrin-coated pit (CCP) formation occurs as a result of the targeting and assembly of cytosolic coat proteins, mainly the plasma membrane clathrin-associated protein complex (AP-2) and clathrin, to the intracellular face of the plasma membrane. In the present study, the mechanisms by which Eps15, an AP-2-binding protein, is targeted to CCPs was analyzed by following the intracellular localization of Eps15 mutants fused to the green fluorescent protein. Clathrin-coated vesicle formation represents the initial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
109
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 97 publications
(120 citation statements)
references
References 54 publications
11
109
0
Order By: Relevance
“…This difference probably accounts for the fact that our ␣ 793-939 lacked the binding site (including at least residues 703-756) for Eps15 (48), one of the accessory proteins involved in clathrin coat assembly on the plasma membrane. Several lines of evidence showed that Eps15 interacts with the appendage domain of ␣-adaptin via its DIII domain, and overexpression of this domain therefore inhibits both clathrin coat assembly and Tfn uptake (49,50). Indeed, we found that GFP-Eps15DIII can bind to the appendage domain of ␣-adaptin (700 -939 amino acids) containing the DIII binding site, but not to ␣ 793-939 (supplemental Fig.…”
Section: ␣-Adaptin-dependent Hm124 Endocytosismentioning
confidence: 78%
“…This difference probably accounts for the fact that our ␣ 793-939 lacked the binding site (including at least residues 703-756) for Eps15 (48), one of the accessory proteins involved in clathrin coat assembly on the plasma membrane. Several lines of evidence showed that Eps15 interacts with the appendage domain of ␣-adaptin via its DIII domain, and overexpression of this domain therefore inhibits both clathrin coat assembly and Tfn uptake (49,50). Indeed, we found that GFP-Eps15DIII can bind to the appendage domain of ␣-adaptin (700 -939 amino acids) containing the DIII binding site, but not to ␣ 793-939 (supplemental Fig.…”
Section: ␣-Adaptin-dependent Hm124 Endocytosismentioning
confidence: 78%
“…To determine whether ␤-arrestin and TRHR traffic together as a complex after receptor stimulation in our model, their relative cellular distributions were studied by immunofluorescence microscopy. The images shown focus on the plasma membrane of cells that are adherent to the coverslip as described previously (32). Under basal conditions, ␤-arrestin2 displayed a characteristic diffuse cytosolic distribution (39) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…For immunofluorescence studies, HeLa cells were seeded on coverslips in six-well plates, transfected with 2 g of VSV-TRHR and 0.2 g ␤-arrestin2-GFP the following day, and used for immunofluorescence 1 day post-transfection. Cells were fixed and processed for fluorescence microscopy as described previously (32). Endocytosis of Alexa594-conjugated Tf was performed on HeLa cells grown on coverslips 1 day after transfection.…”
Section: Methodsmentioning
confidence: 99%
“…Immunocytochemistry-Immunocytochemistry was performed as described previously (26,27). Primary antibodies included anti-transferrin receptor (TfR) (CD71) and anti-␥-adaptin 100.3 and anti-␤-adaptins 100.1 mouse monoclonal antibodies (Sigma), anti-CALM (C-18) and anti-Epsin (R-20) goat polyclonal antibodies (Santa Cruz Biotechnology, Santa Cruz, CA), anti-clathrin (derived from the CON.1 hybridoma (ATCC, Manassas, VA)) and anti-Eps15 (3T, a gift of Dr. Pier Di Fiore, European Institute of Oncology, Milan, Italy).…”
Section: Methodsmentioning
confidence: 99%